Study of flow over piano key weir of different plan shapes with free and partially submerged outlet conditions - Abhash A.; Pandey K.K.; Tripathi R.P. (My University, 2025)
Piano key weirs are being increasingly used for better flood passage downstream, both as a new structure or on top of hydraulic structures like a dam, to increase their discharging capacity as well as reservoir storage. Much research has been done on rectangular plan-form, while other plan-forms warrant attention. The present study focuses on two different plan geometries of PKW, i.e., rectangular (RPKW) and trapezoidal with angle α equal to 9 degrees (TPKW9) for their head-discharge relation in a wide channel of 0.984 m width under free-flow condition. Since the role of CFD is increasingly becoming prominent in present times, a numerical study using ANSYS-FLUENT was also carried out to ascertain its relevance in predicting flows around complex structures like PKW. Further, the tailgate was closed to render the PKW's outlet from partial to fully submerged conditions. The effect of these submerged outlets was studied for any changes in the discharging capacity of the PKW. The study shows RPKW to be more hydraulically efficient than TPKW9 for the model geometry. Further, the study finds that under partial to full submergence of PKW outlets, both PKW units' discharging capability remains unchanged. © 2021 The Authors Water Supply